2016
DOI: 10.1227/neu.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in Cardiomyopathy Genes Associated With Stress-Induced Cardiomyopathy

Abstract: Background Stress-induced cardiomyopathy (SIC) is a poorly understood condition associated with periods of emotional and physical stress. The clinical approaches for management of SIC are supportive and reactive to patient symptoms. Objective To utilize next-generation exome sequencing to define genetic variation associated with, and potentially responsible for, this disease. Methods We performed exome sequencing of 7 white female patients with SIC. Filtering of the identified variants was performed to lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The specific variant we identified in SCN5A, R376L, has not been described in the literature, but the SCN5A H558R variant has been associated with TTC in a genome-wide association study, suggesting a possible association. 4 However, the coexistence of TTC and the genetic variant in the SCN5A gene likely is coincidental, and we have no data supporting an association between the variant, BrS, and occurrence of TTC. This highlights the uncertainty that follows the interpretation of genetic findings, which should be made clear to the patient by the physician before performing genetic testing.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The specific variant we identified in SCN5A, R376L, has not been described in the literature, but the SCN5A H558R variant has been associated with TTC in a genome-wide association study, suggesting a possible association. 4 However, the coexistence of TTC and the genetic variant in the SCN5A gene likely is coincidental, and we have no data supporting an association between the variant, BrS, and occurrence of TTC. This highlights the uncertainty that follows the interpretation of genetic findings, which should be made clear to the patient by the physician before performing genetic testing.…”
Section: Discussionmentioning
confidence: 65%
“…3 The first genome-wide association study (GWAS) conducted on a cohort of 96 patients with TTC found some potential genetic risk variants but the study was too small to be conclusive. 11 Variants in genes associated with various cardiomyopathies have been identified in patients with TTC, 4 but genetic variants associated with electrical disturbances have also been described. A case report described TTC in a patient with long QT syndrome (LQTS) and a genetic variant in the KCNH2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, an exome sequencing study was performed on seven female sporadic TTS patients [ 48 ], evidencing in all subjects predicted deleterious variants in described cardiomyopathy genes. The variants were not described in public human genome data or in a public database associated with cardiac dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Kalani group performed exome sequencing of 7 female sporadic patients with TTS [38]. Exome-sequencing analysis revealed that each patient carried predicted deleterious variants affecting known cardiomyopathy genes.…”
Section: Sequencing Of Takotsubo Cohortmentioning
confidence: 99%